Appropriateness of Proton-Pump Inhibitor Usage among Hospitalized Patients in a Johor Government Hospital - Lee, Tiong Chan (IIUM Medical Journal Malaysia, 2022)
Introduction: Proton pump inhibitors (PPIs) are potent and effective acid suppressant agents. There are emerging concerns that PPI overuse leads to escalating healthcare costs, drug-drug interactions, and adverse clinical outcomes. Exploring the appropriateness of PPI therapy among hospitalised patients in Malaysia is crucial. Thus, this study aims to determine the appropriateness of proton pump inhibitors utilisation in Sultan Ismail Hospital, Malaysia. Materials and Methods: This single-center retrospective cross-sectional study was conducted at a public tertiary hospital situated in the Johore state of Malaysia. Patients recruited were 12 years and above who had received PPI in January 2017. Medical information was reviewed from electronic medical records. Patients were classified into three subgroups based on indications adopted from evidence-based guidelines. Results: 422 patients were enrolled, 47.4% (n=200) fulfilled the Food Drug Administration (FDA) approved indications, 25.4% (n=107) had borderline indications, and 27.2% (n=115) had inappropriate PPI usage. Improper PPI therapy was observed with a similar fraction of patients in medical (24.5%, n= 58 ) and non-medical disciplines (30.8 %, n=57). Stress ulcer prevention in low-risk subjects and individuals with no apparent indication were reasons for PPI overuse. Conclusion: PPI overuse is prevailing in hospitalised adult patients. Promoting the awareness of guideline-based indications and adverse clinical events of PPI among clinicians is imperative in improving PPI prescribing.